2017
DOI: 10.1093/jjco/hyx112
|View full text |Cite
|
Sign up to set email alerts
|

Development of high-grade osteosarcoma in a patient with recurrent giant cell tumor of the ischium while receiving treatment with denosumab

Abstract: Malignant transformation of giant cell tumor of bone (GCTB) without radiotherapy exposure is exceptionally rare, occurring in less than 1% of GCTBs. The safety and efficacy of denosumab in patients with GCTB was recently reported. We herein report a case of a benign recurrent GCTB with an H3F3A mutation that underwent secondary malignant transformation during treatment with denosumab. A 29-year-old woman underwent curettage of a GCTB of the left ischium in 2005. Ten years after the first surgery, the GCTB recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…Malignant transformation of giant cell tumour of the bone is an extremely rare disease that has been defined mainly by pathological features. A review of literature shows cases of giant cell tumour that have undergone malignant transformation to osteosarcoma are being reported 9–11. Our case would add to these growing body of cases.…”
Section: Discussionmentioning
confidence: 65%
“…Malignant transformation of giant cell tumour of the bone is an extremely rare disease that has been defined mainly by pathological features. A review of literature shows cases of giant cell tumour that have undergone malignant transformation to osteosarcoma are being reported 9–11. Our case would add to these growing body of cases.…”
Section: Discussionmentioning
confidence: 65%
“…Seven months after surgical excision, the patient developed an osteosarcoma in the same site, along with pulmonary metastasis. Tsukamoto et al ( 59 ) demonstrated a 25-year-old woman with recurrent GCTB in her left ischium developed a high grade osteosarcoma. She received denosumab therapy for 6 months.…”
Section: Denosumab May Arouse the Malignant Transformation Of Gctbmentioning
confidence: 99%
“…The potential mechanisms of sarcomatous transformations of GCTB following denosumab therapy are probably associated with its actions against RANKL ( 59 ). Although the exact molecular basis is poorly defined, three possible hypotheses are proposed.…”
Section: Denosumab May Arouse the Malignant Transformation Of Gctbmentioning
confidence: 99%
“…The efficacy of denosumab has been demonstrated in patients with unresectable or recurrent GCT of bone, according to the NCCN guideline and previous studies [43]. However, denosumab did not show any effect on reducing the recurrence rate [44], and complications such as sarcomatous transformation should be considered [45]. Fourthly, our findings are only based on the respective data from our institution, this implies a study selection bias that must be acknowledged, and which might only reflect surgeon or patient preference.…”
Section: Comparison Of Complications With Henderson Classificationmentioning
confidence: 99%